2020
DOI: 10.1073/pnas.2004998118
|View full text |Cite
|
Sign up to set email alerts
|

A rate threshold mechanism regulates MAPK stress signaling and survival

Abstract: Cells are exposed to changes in extracellular stimulus concentration that vary as a function of rate. However, how cells integrate information conveyed from stimulation rate along with concentration remains poorly understood. Here, we examined how varying the rate of stress application alters budding yeast mitogen-activated protein kinase (MAPK) signaling and cell behavior at the single-cell level. We show that signaling depends on a rate threshold that operates in conjunction with stimulus concentration to de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 62 publications
1
24
0
Order By: Relevance
“…Step changes in a stress signal induce both a general and a stress-specific response, while ramp changes induce only a stress-specific response ( 56 ). Similar responses to the rate of environmental change have been found to occur in other organisms ( 56 58 ). While dynamic features of environmental signals, such as the frequency of the input or the rate of change, are difficult to measure in natural systems, microfluidic devices can be used to determine whether individual bacteria can process temporal patterns in the input signal in different ways ( 23 ).…”
Section: Processing Of Environmental Signals At the Scale Of Individu...supporting
confidence: 73%
“…Step changes in a stress signal induce both a general and a stress-specific response, while ramp changes induce only a stress-specific response ( 56 ). Similar responses to the rate of environmental change have been found to occur in other organisms ( 56 58 ). While dynamic features of environmental signals, such as the frequency of the input or the rate of change, are difficult to measure in natural systems, microfluidic devices can be used to determine whether individual bacteria can process temporal patterns in the input signal in different ways ( 23 ).…”
Section: Processing Of Environmental Signals At the Scale Of Individu...supporting
confidence: 73%
“…A recent report has demonstrated that the high osmolarity glycerol (HOG) MAPK in yeast is also sensitive to the rate at which osmotic stress is applied. 38 It is likely that slow increases in osmostress do not immediately threaten cellular fitness and can be compensated for by existing cellular mechanisms to restore turgor pressure that do not require HOG pathway activation; therefore, a rate threshold may serve to conserve cellular resources for more significant perturbations. Intriguingly, the HOG pathway ramp sensitivity comes from a negative feedback mechanism whereas one of the mechanisms at play here involves pathway desensitization through receptor loss.…”
Section: Discussionmentioning
confidence: 99%
“…The high osmolarity glycerol (HOG) MAPK pathway in the budding yeast Saccharomyces cerevisiae ( Figure 3A ) is an ideal model system ( Brewster et al, 1993 ; Saito and Posas, 2012 ; Brewster and Gustin, 2014 ) for addressing the question how do rate sensitivity and rate thresholds impact cell signaling and phenotype ( Thiemicke et al, 2019 ; Jashnsaz et al, 2020 ; Johnson et al, 2021 ). At the molecular level, pioneering studies found that one signaling branch is activated through the Synthetic Lethal of N-end rule (Sln1) osmosensing histidine protein kinase leading to activation of the MAPKKK’s Suppressor of Sensor Kinase (Ssk2) and its paralog Ssk22 and converging on the MAPKK Polymyxin B Sensitivity (Pbs2) kinase through several intermediate proteins.…”
Section: Concentration and Rate Thresholds Regulate Yeast Stress Resp...mentioning
confidence: 99%
“…This knowledge of the Hog1 pathway was established through acute osmotic stress concentration increases that induce Hog1 phosphorylation, activation, and translocation to the nucleus ( Figures 3A, B ) ( Brewster et al, 1993 ; Ferrigno et al, 1998 ; Reiser et al, 1999 ; Hersen et al, 2008 ; Macia et al, 2009 ; Muzzey et al, 2009 ; Pelet et al, 2011 ; Saito and Posas, 2012 ; English et al, 2015 ; Mitchell et al, 2015 ; Granados et al, 2017 ). Activated Hog1 controls the regulation of cellular osmoadaptation and survival ( Saito and Posas, 2012 ; Mitchell et al, 2015 ; Johnson et al, 2021 ). Because of this behavior of Hog1 nuclear enrichment, single-cell time-lapse microscopy and analysis have proven an excellent and sensitive way to monitor signaling responses to dynamic stimulation patterns in real-time ( Figure 3 ) ( Hersen et al, 2008 ; Mettetal et al, 2008 ; Muzzey et al, 2009 ; Patterson et al, 2010 ; Munsky et al, 2012 ; Mitchell et al, 2015 ; Granados et al, 2017 ; Thiemicke et al, 2019 ; Jashnsaz et al, 2021 ; Johnson et al, 2021 ).…”
Section: Concentration and Rate Thresholds Regulate Yeast Stress Resp...mentioning
confidence: 99%